Protecting heritage in the Caribbean - Siegel, Peter E.; Righter, Elizabeth, 1937- (Caribbean archaeology and ethnohistory., 2011)
Heritage preservation is a broad term that can include the protection of a wide range of human-mediated material and cultural processes ranging from specific artifacts, ancient rock art, and features of the built environment and modified landscapes. As a region of multiple independent nations and colonial territories, the Caribbean shares a common heritage at some levels, yet at the same time there are vast historical and cultural differences. Likewise, approaches to Caribbean heritage preservation are similarly diverse in range and scope. This volume addresses the problem of how Caribbean.